The Correlation Analysis Between Critical Thinking Skills And Learning Outcomes Through Implementation Of Guided Inquiry Learning Models - Laiaza Aghenia Muhan; Harun Nasrudin (Pendidikan Kimia Unimus, 2021)
The 21st-century learning process highlights the critical thinking skills concept. Critical thinking has the highest chance of impacting students' learning outcomes. One of the learning models to increase critical thinking skills was guided inquiry. This research aimed to analyze the correlation between critical thinking skills and learning outcomes on reaction rates topic using the Guided Inquiry learning model. This research used a correlational design. Subjects were students of SMA Negeri 1 Krian class XI MIPA 6 odd semester in the academic year 2020/2021 as many as 34 people. The data were obtained using the observation sheets instrument for the implementation of the guided inquiry learning model, the critical thinking skills test sheets, and the learning outcomes test sheets. Data were analyzed using Pearson correlation and linear regression analysis used (α) 0.05. The results indicated that there was a significant positive correlation between critical thinking and learning outcomes on reaction rates topic using the Guided Inquiry learning model. The correlation regression equation obtained between the two variables is Y = -16.575 + 1.170X with reliability value 76,3%. The N-gain score obtained for each indicator of critical thinking skills and learning outcomes ≥ 0.7 at high criteria.